Inequality of income acquisition: The role of childhood circumstances - Paul Hufe; Andreas Peichl; John Roemer; Martin Ungerer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Many studies have estimated the effect of circumstances on income acquisition. Perhaps surprisingly, the fraction of inequality attributable to circumstances is usually quite small - in the advanced democracies, on the order of 20%. One reason for this is the lack of data on circumstance variables in empirical research. Here, we argue that all behaviors and accomplishments of children should be considered the consequence of circumstances: That is, an individual should not be considered to be responsible for her choices before an age of consent is reached. Using two data sets that contain data on childhood accomplishments, other environmental circumstances, and the income as an adult, we compute that the fraction of income inequality due to circumstances in the US is over 45%, and in the UK it is over 31%.
Keywords: D63; D3; 330; Equality of Opportunity; Earnings Inequality; Lower bounds; Early childhood achievements